Women’s Language Features in Turning Red (2022): A Sociolinguistics Study - Kintan Utari Juanda; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
Women and men have different ways of using language, which makes women have their own features called women’s language features. This study examines the use of women’s language features in Turning Red (2022). The study aims to analyze women’s language features used by the female lead character in Turning Red (2022) based on its types according to Lakoff (1975) and its functions according to Jakobson (1960). The study employed a qualitative method with a descriptive approach in interpreting the data. Among the 170 data analyzed, 9 out of 10 women's language features were identified. These include hypercorrect grammar (26.5%), lexical hedges or fillers (22%), emphatic stress (19%), intensifiers (16.5%), avoidance of strong swear words (4.7%), super polite forms (4%), tag question (3%), empty adjectives (2.4%), and rising intonation on declarative (1.9%). Notably, the presence of precise color terms features is absent from the data. Furthermore, the analysis uncovered 5 out of 6 language functions, namely referential (39.4%), expressive (38%), phatic (16%), directive (6%), and poetic function (0.6%). It is worth noting that no instances of the metalinguistic function were found within the analyzed data. This study is expected to enhance comprehension regarding women’s language features, while also serving as a valuable resource for both educational purposes and further research in the field of linguistics, specifically within the realm of sociolinguistics.